(untitled) (Research, Society and Development, 2022)
The regular practice of resistance training is directly related to lean mass gains, strength, physical conditioning, quality of life and others. For such gains to occur, an evaluation and prescription process is necessary. The objective of this research was to verify the general prerequisites and criteria used during the process of determining the load control in resistance training, common to this modality of physical intervention. Studies were researched in Science Direct, PUBMED and IBCS, published from 2017 to 2022. After analyzing the selected works, the present study brings a synthesis of information about the variables involved in the prescription referring to load control for RT, adapting the manipulation of the variables involved in the resistance training session, which may interfere. At the end of the analysis of the selected works, it is possible to relate the main criteria related to load control in TR, it is clear the benefits and safety in training for strength, resistance and lean mass gains, among others.